Manajemen Strategik dalam Meningkatkan Mutu Pendidikan di MTs Bina Insani Way Kanan - Zamroni, Ahmad; Ardianto, Medi Romi (Attractive : Innovative Education Journal, 2022)
This study aims to determine the process of planning, implementing and evaluating strategic management in improving the quality of education at MTs Bina Insani Way Kanan. The type of data collected in this study consisted of 2 data, namely: primary data and secondary data. The methods used in data collection are: Observation, Interview and Documentation. The data analysis technique uses Miles and Huberman, suggesting that the activities in qualitative data analysis are carried out interactively and continuously until complete, so that the data is saturated. Activities in data analysis, namely data reduction, data display, and conclusion drawing/verification. The results of the study can be concluded that strategic management in improving the quality of education at MTs Bina Insani Way Kanan, shows that: (1) Strategic planning at MTs Bina Insani Way Kanan includes four activities, namely developing vision, mission and goals, short, medium and long term planning. length, identification of internal and external factors, and formulation of strategies. (2) The implementation of strategic management at MTs Bina Insani Way Kanan includes four activities, namely determining madrasah policies, motivating educators and education staff, allocating human resources, and developing a strategic culture. (3) Evaluation of strategic management at MTs Bina Insani Way Kanan includes three activities, namely monitoring all results, measuring individual and madrasah performance, taking corrective steps Keywords: Management Strategy, Improving Education Quality, Education Quality